Cardiac changes in moderately malnourished children and their correlations with anthropometric and electrolyte changes. Issue 11 (12th September 2017) - El Razaky, Osama; Naeem, Ahmed; Donia, Amr; El Amrousy, Doaa; Elfeky, Noha
Abstract : Objective: To evaluate electrocardiographic and echocardiographic changes in moderately malnourished children and to correlate them with both anthropometric and electrolyte changes. Patients and method: Sixty moderately malnourished children were taken as patient group, and 60 healthy children of matched age and sex were taken as control group. Weight, height, body mass index (BMI), serum albumin, and electrolytes were measured for all children. Electrocardiographic evaluation for calculated QT (QTc) and QT dispersion (QTd) was performed. Left ventricular (LV) function was also evaluated using conventional echocardiography, tissue Doppler, and strain methods. Left ventricular mass index (LVMI) was also calculated. Results: Weight, BMI, serum levels of albumin, total calcium, and ionized calcium were significantly lower, while QTc and QTd were significantly prolonged in malnourished children ( P = .001 for all). There was significant reduction in LV fraction shortening (FS), LV Eʹ/Aʹ, LV strain (S), LV myocardial performance index (MPI), LV global systolic strain (GLSS), and LVMI ( P = .001 for all) in malnourished children. There was significant correlation between BMI and all cardiac variables. Moreover, there was significant positive correlation between serum albumin level and LV Eʹ/Aʹ ( P = .02), LV GLSS ( P = .03), and LVMI ( P = .03).Total and ionized calcium level were significantly correlated with QTc, QTd, and LVMI ( P < .05 for all). BMI was the most powerful predictor of these electrocardiographic and echocardiographic changes. Conclusion: Cardiac changes were present in moderately malnourished children as documented by electrocardiographic and echocardiographic changes, and these changes are in strong association with BMI and for a lesser extent with electrolyte changes especially serum calcium.